2007
DOI: 10.1177/1076029606296405
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparative Study of Three Sets of Criteria for Disseminated Intravascular Coagulation: ISTH Criteria vs Japanese Criteria

Abstract: Clinical and laboratory criteria and a scoring system for disseminated intravascular coagulation (DIC) were recently published by the International Society on Thrombosis and Haemostasis (ISTH). In Japan, the DIC Diagnostic Standards published in 1988 have been widely used for more than 10 years. In a general intensive care unit, we prospectively compared the diagnostic properties of the overt DIC, nonovert DIC, and Japanese DIC criteria sets, and investigated the influences of each set on patient morbidity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…On the other hand, we found that the non-overt DIC criteria were unable to diagnose DIC earlier than the old Japanese criteria (2). The non-overt DIC criteria are not sufficient for the early diagnosis and treatment of DIC (2).…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…On the other hand, we found that the non-overt DIC criteria were unable to diagnose DIC earlier than the old Japanese criteria (2). The non-overt DIC criteria are not sufficient for the early diagnosis and treatment of DIC (2).…”
mentioning
confidence: 58%
“…Previously we reported a prospective comparison between the ISTH criteria and the old Japanese criteria (2). We showed that both the non-overt DIC and old Japanese criteria accurately predicted outcomes (2). On the other hand, we found that the non-overt DIC criteria were unable to diagnose DIC earlier than the old Japanese criteria (2).…”
mentioning
confidence: 58%
See 3 more Smart Citations